Subtitling Analysis Of Sentences In Everest Movie - Azhari, Rifki Adhin; , Dr. Dwi Haryanti, M.Hum (2016)
This research aims at (1) classifying the types of sentence in Everest movie and its translation (2) describing the accuracy of the subtitling in Everest movie. The type of this research is descriptive qualitative research. The data of this study are the declarative, interrogative, and imperative sentences in Everest movie and their translation in Indonesian and the data source are movie script of English and Indonesian entitled Everest movie. The researcher uses documentation and interview to collect the data. Then, to prove the validity of data, the writer uses triangulation where the data sources are from subtitle and its translation, and informant. The result of the research shows that from 1232 data, there are 805 data or 65.34% belong to declarative sentence is translated into declarative sentence, 2 data or 0.16% belong to declarative sentence is translated into interrogative, 10 data or 0.81 belong to declarative sentence is translated into imperative sentence, 207 data or 16.8% belong to interrogative sentence is translated into interrogative sentence, 11 data or 0.89% belong to interrogative sentence is translated into declarative sentence, 7 data or 0.57% belong to interrogative sentence is translated into imperative sentence, 185 or 15.02% belong to imperative sentence is translated into imperative sentence, 4 data or 0.32% belong to imperative sentence is translated into declarative sentence, and 1 datum or 0.08% belongs to imperative sentence is translated into interrogative sentence. The accuracy of the data shows that 1149 data or 93.27% are accurate, 50 data or 4.06% are less accurate, and 33 data or 2.67% are inaccurate.